The effects of COVID-19 home confinement on the psychological well-being of the Moroccan population: Regular versus irregular dynamics. - Hicham KHABBACHE; Laila EL ALAMI; Khalid OUAZIZI; Driss AIT ALI; Hanane EL GHOUAT; Mohamed MAKKAOUI; Mimoun SAIDI; Abdelilah EL MENIARI; Kawtar KHABBACHE; Eman SHENOUDA; Radouane MRABET; Abdelhalim CHERQUI; et al. (Journal of Health and Social Sciences)
Background: Amidst the COVID-19 pandemic and the implementation of home confinement measures, understanding the psychological well-being of individuals has become crucial. Aim: This study examines the irregular effects of gender, age, marital status, and educational level on the psychological well-being of the Moroccan population during COVID-19 home confinement. Design: A cross-sectional study design was utilized. Setting: The study was conducted online, with participants residing in Morocco. Population: The study included individuals from the Moroccan population (n=1.051) who experienced home confinement during the COVID-19 pandemic. Methods: Data was gathered through an anonymous psychological well-being scale administered online. Results: Data analysis revealed three underlying traits: The first is the unexpected impact of age, gender, education levels, and marital status on certain well-being parameters. The second is the varied impact of gender, specifically in its interaction with age and marital status. The varied impact was also reflected in the participants’ mean scores across the well-being parameters. The third indicator revealed the nonlinear impact of the education level on some well-being parameters. Conclusion: The study drew the attention of public health decision-makers to the need to include different scenarios in the elaboration of anticipatory plans in the case of a new pandemic and to avoid sticking to regular models based on regular scenarios only.